IMPLEMENTASI ADMINISTRASI PEMBELAJARAN DALAM MENINGKATKAN EFEKTIVITAS PROSES BELAJAR-MENGAJAR DI SMP AL-AMANAH SETU - Amelia, Nanda; Musdhalifa, Eva; Della, Salsabila Alfa; Nisa, Usfatun (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study examines the implementation of learning administration as an effort to enhance the effectiveness of the teaching and learning process at SMP Al-Amanah Setu. Learning administration includes key instructional documents such as lesson plans (RPP), annual programs (Prota), semester programs (Promes), and daily teaching journals, which serve as guidelines for teachers in organizing, delivering, and evaluating learning activities. The research employed a qualitative approach with a descriptive case study design. Data were obtained through in-depth interviews, non-participant classroom observations, and document analysis involving the school principal, vice principal for curriculum, subject teachers, and administrative staff. Data analysis followed the interactive model proposed by Miles and Huberman, consisting of data reduction, data presentation, and conclusion drawing. The results reveal that learning administration at SMP Al-Amanah Setu has been implemented in an organized manner and has positively influenced the effectiveness of the teaching and learning process, as reflected in increased student engagement, improved attainment of learning objectives, and more efficient management of time and resources. Nevertheless, challenges such as teachers’ heavy administrative workload and limited periodic supervision were identified.